2022
DOI: 10.1111/psyp.14162
|View full text |Cite
|
Sign up to set email alerts
|

ERP responses to sexual cues among young women attracted to men

Abstract: Previous event‐related potential (ERP) studies reported larger N170, P3, and late positive potential (LPP) amplitudes to sexual than nonsexual stimuli. These ERPs may not be specifically sensitive to processing sexual cues, however, because the sexual stimuli included information beyond sexual cues (e.g., faces, bodies, social interaction) to a greater extent than comparison stimuli. We investigated ERPs to stimuli that focused on sexual and nonsexual body regions, in different states of readiness for activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Furthermore, interactive effects of SE/SI might be more pronounced when used stimuli depict aspects of sexual interactions directly related to SI (e.g., pain, judgement, risk of pregnancy/STDs), or SE (e.g., unusual settings, dominance). Hence, using a greater variety of sexuality-related stimulus material (positive, negative, high vs. low in context details), or more explicit stimuli depicting different stages of sexual readiness ( Huberman et al, 2023 ), would be insightful. In this regard, implicit measures of stimulus processing could be paired with explicit stimulus evaluations (i.e., valence and arousal ratings).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, interactive effects of SE/SI might be more pronounced when used stimuli depict aspects of sexual interactions directly related to SI (e.g., pain, judgement, risk of pregnancy/STDs), or SE (e.g., unusual settings, dominance). Hence, using a greater variety of sexuality-related stimulus material (positive, negative, high vs. low in context details), or more explicit stimuli depicting different stages of sexual readiness ( Huberman et al, 2023 ), would be insightful. In this regard, implicit measures of stimulus processing could be paired with explicit stimulus evaluations (i.e., valence and arousal ratings).…”
Section: Discussionmentioning
confidence: 99%
“…To enhance our understanding of the attentional and motivational dynamics underlying SE/SI, the use of ERPs constitutes a particularly well-suited and advantageous technique. The high temporal resolution of ERP components and their well-described associations with specific cognitive and emotional processes ( Hajcak et al, 2010 ), including those associated with erotic stimulus processing ( Huberman et al, 2023 ), allow for the specific identification of different phases of stimulus processing affected by tendencies for SE/SI. So far, however, the study from Aguiar et al (2023) was the only one to apply an ERP-based approach to assess neural correlates of the DCM framework.…”
Section: Introductionmentioning
confidence: 99%
“…There is a small EEG literature that assesses neural responses to sexual rather than monetary stimuli. For example,Huberman and colleagues [55] identi ed several components of the event-related brain potential (ERP) called the P300 and anterior N270-400 that are sensitive to sexual readiness such that they uctuate in response to viewing an erect versus accid penis. Prause and colleagues [56] found changes in an ERP component called the late positive potential (LPP) in response to explicit versus non-explicit sexual images-which varied based on individual differences in number of sexual intercourse partners.…”
Section: Previous Research On Adversity and Reward Sensitivitymentioning
confidence: 99%
“…There is a small EEG literature that assesses neural responses to sexual rather than monetary stimuli. For example, Huberman et al 58 identified several components of the event-related brain potential (ERP) called the P300 and anterior N270-400 that are sensitive to sexual readiness such that they fluctuate in response to viewing an erect versus flaccid penis. Prause et al 59 found changes in an ERP component called the late positive potential (LPP) in response to explicit versus non-explicit sexual images—which varied based on individual differences in number of sexual intercourse partners.…”
Section: Introductionmentioning
confidence: 99%